Amr al-Awzai Research. - Judd, Steven (2004)
Keywords: dept.his; faculty_collection; sabbatical_report

Northern Treasures and Southern Essences, an Exploration of Vietnamese Traditional Medicine. - Thompson, C. Michele (2004)
Keywords: dept.his; faculty_collection; sabbatical_report

In defense of homology and history: A response to Allen - Paddock, T. (Philosophy and Geography, 2004)
Keywords: dept.his

Dobra ruska miza, slaba ruska miza - Thomas Mann in nemški orientalizem - Paddock, Troy R. E. (Borec, 2004)
Keywords: dept.his; ⛔ No DOI found

A Call to Arms: Propaganda, Public Opinion, and Newspapers in the Great War - Paddock, Troy R. E. (Perspectives on the twentieth century, 2004)
World War I highlighted the influence of newspapers in rousing and maintaining public support for the war effort. Discussions of the role of the press in the Great War have, to date, largely focused on atrocity stories. This book offers the first comparative analysis of how newspapers in Great Britain, France, Russia, Germany, and Austria-Hungary attempted to define war, its objectives, and the enemy. Presented country-by-country, expert essays examine, through use of translated articles from the contemporary press, how newspapers of different nations defined the war for their readership and t., World War I highlighted the influence of newspapers in rousing and maintaining public support for the war effort. Discussions of the role of the press in the Great War have, to date, largely focused on atrocity stories. This book offers the first comparative analysis of how newspapers in Great Britain, France, Russia, Germany, and Austria-Hungary attempted to define war, its objectives, and the enemy. Presented country-by-country, expert essays examine, through use of translated articles from the contemporary press, how newspapers of different nations defined the war for their readership and t
Keywords: Press coverage; Propaganda; World War, 1914-1918; Public opinion; Press and propaganda; War; World War, 1914-1918; dept.his; faculty_collection

Trusteeship and black landownership in the Transvaal during the nineteenth and twentieth centuries - Bergh, J S; Feinberg, Harvey M (African Historical Review, 2004)
Keywords: dept.his

Book Review: Two approaches to introductory middle east history - the middle east: A history , 6th edition, by william ochsenwald and sidney nettleton fisher. new york: McGraw hill, 2004. 780 pages, glossary, index. US59.30 (paper) ISBN 0-07-244233-6 - the levant: A fractured mosaic , by william harris. princeton: marcus weiner, 2003. 211 pages, glossary, index. US22.95 (paper) ISBN 1-55876-265-5 - Judd, Steven (Middle East Studies Association Bulletin, 2004)
Keywords: book.review; dept.his

Chosen peoples: sacred sources of national identity - Paddock, Troy (History: Reviews of New Books, 2004)
Keywords: dept.his

Gedachtes wohnen: Heidegger and cultural geography - Paddock, Troy (Philosophy & Geography, 2004)
Keywords: cultural geography; dept.his

Imagining the nation in nature: landscape preservation and German identity, 1885–1945: Lekan, Thomas M.: Cambridge, MA: Harvard University Press, 334 pp., publication date: February 2004 - Paddock, Troy (History: Reviews of New Books, 2004)
Keywords: book review; dept.his